IMPLIKASI ALIH FUNGSI TANAH PERTANIAN TERHADAP KESEJAHTERAAN PETANI DI DESA TEMPEL KECAMATAN GATAK KABUPATEN SUKOHARJO - Kurniawan, Andri (PKn Progresif, 2015)
The objectives of research are find out: 1) policy over the function of farmland in Sukoharjo Regency, 2) factors that cause the occurrence of function of agricultural land and the implications of agricultural land on the welfare functions of the farmers in the village of paste, 3) the solution improved the well-being of farmers in the village of paste after control of the functions of agricultural land after going over the function of soil. This study was a descriptive qualitative method. The research strategy used was a single embedded strategy. The data source was obtained from informant, event/activity and document. The sampling technique used was purposive sampling. Techniques of collecting data used to obtain and to organize the data of research were interview, observation as well as document analysis. To validate the data, the data triangulation was used. Meanwhile the technique of analyzing data used was an interactive model of analysis with the following steps: 1) Data collection, 2) Data reduction, 3) Data display, 4) Conclusion drawing/verification. The procedure of research included: 1) preparation, 2) data collection, 3) Data analysis, and 4) Research report writing stages.